Struggles for belonging citizenship in Europe, 1900-2020 - Gosewinkel, Dieter 1956- (Oxford University Press USA - OSO, 2021)
This book recounts the history of citizenship in 20th century Europe, focussing on six countries: Great Britain, France, Germany, Czechoslovakia, Poland, and Russia. It is the history of a central legal institution that significantly represents and at the same time determines struggles over migration, integration, and belonging
Keywords: Geschichte 1900-2020; Staatsbürger; Staatsangehörigkeit; Europa; Citizenship / Europe / History / 20th century; Citizenship / Europe / History / 21st century; Electronic books